2009
DOI: 10.2302/kjm.58.133
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Professionalism into Medical Education: The Mayo Clinic Experience

Abstract: Professionalism is a core competency of physicians. In this article, the statements of professional societies (e.g., the Charter on Medical Professionalism), the expectations of patients and society regarding professionalism, and a framework for defining medical professionalism are described. The framework's foundation consists of clinical competence, communication skills, and a sound understanding of the ethical and legal aspects of medicine. Rising from this foundation are attributes of professionalism: acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
113
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 33 publications
2
113
0
4
Order By: Relevance
“…Definitions of altruism as determined by action echoes iterations of altruism as a behaviour (Coulter et al, 2007;Glannon and Ross, 2002;Mueller, 2009). However, many students conceptualised altruism as an intention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Definitions of altruism as determined by action echoes iterations of altruism as a behaviour (Coulter et al, 2007;Glannon and Ross, 2002;Mueller, 2009). However, many students conceptualised altruism as an intention.…”
Section: Discussionmentioning
confidence: 99%
“…Professionalism has been linked to employee morale and productivity, alongside improved communication and teamwork (Mueller, 2009). Professionalism has also been associated with ensuring patients' trust in doctors (Hilton and Slotnick, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Now it is clearly known that professionalism results in better patient satisfaction and outcomes, is associated with better clinical proficiency in interns, and predicts the incidence of misconduct and malpractice litigation in future clinical practice. 5,15 The frequency of medical errors in the Kingdom of Saudi Arabia was reported to be on the rise. 14 There are a limited number of studies in the literature regarding professionalism among new medical graduates in kingdom of Saudi Arabia and this study is considered one of the first and few quantitative studies that conducted in one of the largest teaching hospital in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…5 In fact, Wofford et al, reported that most of the patient's complaints are about doctors' behaviour, not their lack of knowledge. 6 These findings emphasized the need to ensure competence in professional behaviours and communication skills.…”
mentioning
confidence: 99%
See 1 more Smart Citation